Nanostructured Lipid Carriers as Multifunctional Nanomedicine Platform for Pulmonary Co-Delivery of Anticancer Drugs and siRNA - Taratula, Oleh (2013)
We developed, synthesized, and tested a multifunctional nanostructured lipid nanocarrier-based system (NLCS) for efficient delivery of an anticancer drug and siRNA directly into the lungs by inhalation. The system contains: (1) nanostructured lipid carriers (NLC); (2) anticancer drug (doxorubicin or paclitaxel); (3) siRNA targeted to MRP1 mRNA as a suppressor of pump drug resistance; (4) siRNA targeted to BCL2 mRNA as a suppressor of nonpump cellular resistance and (5) a modified synthetic analog of luteinizing hormone-releasing hormone (LHRH) as a targeting moiety specific to the receptors that are overexpressed in the plasma membrane of lung cancer cells. The NLCS was tested in vitro using human lung cancer cells and in vivo utilizing mouse orthotopic model of human lung cancer. After inhalation, the proposed NLCS effectively delivered its payload into lung cancer cells leaving healthy lung tissues intact and also significantly decreasing the exposure of healthy organs when compared with intravenous injection. The NLCS showed enhanced antitumor activity when compared with intravenous treatment. The data obtained demonstrated high efficiency of proposed NLCS for tumor-targeted local delivery by inhalation of anticancer drugs and mixture of siRNAs specifically to lung cancer cells and, as a result, efficient suppression of tumor growth and prevention of adverse side effects on healthy organs.